الأبداع الفني من منظور النقاد القدامى والمًحْدثين - مصباحي, علي (جامعة الوادي - University of Eloued, 2020)
يعتبر الابداع الفني من القضايا النقدية التي أسالت الكثير من الحبر بين جمهور النقاد والمفكرين لما يكتسيه من أهمية بالغة في الدرس النقدي من جهة ، وباعتباره من الالغاز المُحيرة – إن صح التعبير- التي استعصى على النقاد والباحثين فك شفراته والبحث في أصله وارهاصاته الاولية من جهة اخرى ،ولهذا اختلفت الآراء ووجهات النظر حوله . وهذه المقالة عبارة عن اضاءة عامة تبحث وبدقة في الآراء النقدية حول أصل الابداع وكيفية تبلوره سواء عند النقاد القدامى أو المحدثين والخروج برؤية عامة حول هذا الموضوع لعلها تكون لبية صلبة في الصرح النقدي. Abstract: Artistic creativity is one of the critical issues that have caused a lot of ink among the public of critics and intellectuals because of its great importance in the critical lesson on one hand, and as a puzzling, so to speak, that critics and researchers have deciphered and researched its origin and initials on the other hand, that is why the views have differed about it. This article is a general illumination that thoroughly examines the critical opinions about the origin of creativity and how it crystallizes, whether by old or modern critics, and come up with a general vision on this subject that may be a solid building block in critical edifice.
مقال
Keywords: الابداع ; النقد ; المحدثين ; القدامى ; الشعر ; السيكولوجي